Perkembangan Kehidupan Ekonomi Petani Cabai Nagari Paninjauan Kecamatan X Koto Kabupaten Tanah Datar 2007-2020 - Yesi Aulia Putri; Hendra Naldi (Jurnal Kronologi, 2022)
This study discusses the economic life of chili farmers in Nagari Paninjauan, X Koto District, Tanah Datar Regency in a certain period, the decrease and increase in chili production which has an impact on the level of farmers' welfare. This study aims to explain the economic development of chili farmers from 2007-2020 in Nagari Paninjauan, Tanah Datar Regency. The purpose of this study was to explain the pattern of production and distribution of Nagari Paninjauan chili and to explain the economic conditions of Nagari Paninjauan chili farmers from 2007-2020. This research includes qualitative research, using historical research methods. Qualitative research is a research procedure that produces descriptive data. The steps in historical research go through four stages, namely heuristics (data collection), source criticism, interpretation (interpreting historical evidence) and historiography (historical writing). Data collection techniques used are archive studies, literature studies and interviews. The results showed that, first, the farmers' chili production was sold to collectors who have been partners for a long time. Second, that the ups and downs of chili prices affect the lives of farmers in meeting their daily needs. Keywords: Development, Economy, Chili Farmers